IMPLEMENTASI DIRECT INSTRUCTION MELALUI PENDEKATAN PRILAKU DALAM MENGEMBANGKAN KECERDASAN LINGUISTIK SISWA ADHD PERSPEKTIF TASAWUF - Siti Nurjanah; Agus Sholikhin; Nopiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research examines direct instruction in developing the linguistic intelligence of Attention Deficit Disorders (ADHD) students against the experience of loneliness among students during the move to distance learning and social distancing policies during the COVID-19 pandemic. This study examined multiple serial mediation of students' experiences with distance learning, perceived social support, and hope. We hypothesized that students with ADHD would experience social stress in addition to struggling with distance learning. However, we hope that social support and hope can mediate their loneliness. The sample consisted of students (average age SMA 17.99, – Kindergarten 5.08), at a medium-sized State Special School in East OKU and OKI Districts. Participants were divided into two groups of typical students and ADHD students. Loneliness, negative experiences during the use of distance learning, perceptions of social support, and expectations were examined. Students with ADHD reported higher levels of loneliness and more negative experiences with distance learning than their peers, as well as students' lower language skills. Results showed that ADHD and negative experiences with distance learning predicted higher levels of loneliness, while school support and peer support alongside hopeful thinking mediated this relationship. Discussion focuses on the theoretical and practical aspects of loneliness and support while emphasizing the therapeutic implications of hope. Keywords: Direct Instruction, linguistic intelligence, ADHD students